Master techniques in blepharoplasty and periorbital rejuvenation - Massry, Guy G.; Murphy, Mark R.; Azizzadeh, Babak (Springer New York, 2011)
The eyes are a central feature of facial appearance, expression and provide us the ability to see, our most important sensory function.  For this reason, mastering the evaluation and execution of aesthetic rejuvenation of the eyelids and adjacent areas is critical to all surgeons who operate on these very delicate and interconnected structures. Master Techniques in Blepharoplasty and Periorbital Rejuvenation is a comprehensive, multi-specialty textbook on blepharoplasty and eyelid reconstruction. Special features include: A multidisciplinary view of how this particular area of facial aesthetic surgery is approached and how its associated procedures are performed; Provides a unique and comprehensive understanding of cosmetic brow lifting, blepahroplasty and midface surgery; Written by leading experts in a variety of specialties, including oculoplastic surgery, facial plastic surgery, plastic surgery and dermatology.